Transaction Convenience Terhadap Repurchase Intention Dengan Customer Satisfaction Sebagai Variabel Intervening Dalam Persepektif Bisnis Syariah (Studi Pada Pengguna Mobile Commerce di Mahasiswa UIN RIL) - Evi mayanti; Weny Rosilawati; Supaijo Supaijo (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of the Transaction Convenience variable on Repurchase Intention with Customer Satisfaction as an Intervening Variable among Students using Mobile Commerce at the State Islamic University of Raden Intan Lampung and to see whether Students using Mobile Commerce have an influence on Transaction Convenience on Mobile Commerce, and whether their Intention Repurchasing will have an effect on Transaction Convenience through Customer Satisfaction. This type of research is a quantitative approach. Quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. The sampling technique in this research uses data collection techniques: Library Research and Questionnaires. The research results used a partial hypothesis test (t test) which showed that the Transaction Convenience value had a positive and significant effect on Repurchase Intention. Customer Satisfaction has a positive and significant effect on Transaction Convenience. Customer Satisfaction has a positive and significant effect on Repurchase Intention.